Stakeholder dialogue on dilemmas at work as a workplace health promotion intervention including employees with a low SEP: a Responsive Evaluation - Hanneke van Heijster; Jantien van Berkel; Cécile R. L. Boot; Tineke Abma; Emely de Vet (BMC, 2022)
Abstract Background The aim of this study was to evaluate the perceived changes of an innovative workplace health promotion intervention and evaluation. In this study, a bottom-up approach was taken to define the central themes and relevant outcomes of an intervention. These central themes and relevant outcomes of the intervention were defined together with stakeholders, including employees with a low socioeconomic position. Methods The intervention consisted of a series of structured stakeholder dialogues in which dilemmas around the - by employees defined -health themes were discussed. The intervention was implemented in a harbor service provider with approximately 400 employees. Over a two-year period, 57 participants engaged in eight dialogues of one hour. 15 interviews and six participant observations took place for the evaluation of the intervention. Results Together with the stakeholders, high workload and mental health were defined as central themes for the dialogue intervention in the male-dominated workplace. The dialogue intervention contributed to changes, on different levels: individual, team, and organization. Overall, the stakeholder dialogues advanced the understanding of factors contributing to high workload and mental health. In reply to this, several actions were taken on a organizational level. Conclusions Taking a bottom-up approach in WHP allows to understand the health issues that are important in the daily reality of employees with a low socioeconomic position. Through this understanding, workplace health promotion can become more suitable and relevant for employees with a low socioeconomic position. Trial registration Netherlands Trial Register (NRT): NL8051. Registration date: 28/09/2019, Retrospectively registered https://www.trialregister.nl